Prevalence and Strain Characterization of Clostridioides (Clostridium) difficile in Representative Regions of Germany, Ghana, Tanzania and Indonesia – A Comparative Multi-Center Cross-Sectional Study - Seugendo, Mwanaisha; Janssen, Iryna; Lang, Vanessa; Hasibuan, Irene; Bohne, Wolfgang; Cooper, Paul; Daniel, Rolf; Gunka, Katrin; Kusumawati, R. L.; Mshana, Stephen E.; von Müller, Lutz; Okamo, Benard; et al. (Frontiers in Microbiology, 2018)
Clostridioides (Clostridium) difficile infections (CDI) are considered worldwide as emerging health threat. Uptake of C. difficile spores may result in asymptomatic carrier status or lead to CDI that could range from mild diarrhea, eventually developing into pseudomembranous colitis up to a toxic megacolon that often results in high mortality. Most epidemiological studies to date have been performed in middle- and high income countries. Beside others, the use of antibiotics and the composition of the microbiome have been identified as major risk factors for the development of CDI. We therefore postulate that prevalence rates of CDI and the distribution of C. difficile strains differ between geographical regions depending on the regional use of antibiotics and food habits. A total of 593 healthy control individuals and 608 patients suffering from diarrhea in communities in Germany, Ghana, Tanzania and Indonesia were selected for a comparative multi-center cross-sectional study. The study populations were screened for the presence of C. difficile in stool samples. Cultured C. difficile strains (n=84) were further subtyped and characterized using PCR-ribotyping, determination of toxin production, and antibiotic susceptibility testing. Prevalence rates of C. difficile varied widely between the countries. Whereas high prevalence rates were observed in symptomatic patients living in Germany and Indonesia (24.0%, 14.7%), patients from Ghana and Tanzania showed low detection rates (4.5%, 6.4%). Differences were also obvious for ribotype distribution and toxin repertoires. Toxin A+/B+ ribotypes 001/072 and 078 predominated in Germany, whereas most strains isolated from Indonesian patients belonged to toxin A+/B+ ribotype SLO160 and toxin A-/B+ ribotype 017. With 42.9-73.3%, nontoxigenic strains were most abundant in Africa, but were also found in Indonesia at a rate of 18.2%. All isolates were susceptible to vancomycin and metronidazole. Mirroring the antibiotic use, however, moxifloxacin resistance was absent in African C. difficile isolates but present in Indonesian (24.2%) and German ones (65.5%). This study showed that CDI is a global health threat with geographically different prevalence rates which might reflect distinct use of antibiotics. Significant differences for distributions of ribotypes, toxin production, and antibiotic susceptibilities were observed.